Molecular Symmetry and Art: Visualizing the Near-Symmetry of Molecules in Piet Mondrian's De Stijl - Senge, Mathias (My University, 2024)
Symmetry and shape are essential aspects of molecular structure and how we interpret molecules and their properties. We, as chemists, are comfortable with pictorial representations of structure, in which some nuance is lost— investigating molecular shape numerically by looking at how closely it fits a reference, such as a plane, or a set of vectors or coordinates, is informative, though far from engaging. Often relationships between chemical structure and derived values are obscured. Taking our inspiration from Piet Mondrian’s Compositions, we have depicted the symmetry information encoded within 3D data as blocks of color, to show clearly how chemical arguments and resultant molecular distortion may contribute to symmetry. Great art gives us a new perspective on the world; as a pastiche, this art may allow us to look at familiar molecules, such as porphyrins, in a new light, understanding how their shape and properties are intertwined.